Principles and procedures in the administration of justice - More, Harry W. (Administration of justice series, 1975)
This textbook, intended for the student of criminal justice, provides a concise analysis of the foundations, principles, and procedures of the criminal justice system. The social and legal foundations of justice are first examined. The major components of the criminal justice system -- law enforcement, prosecution, defense, the judiciary, and corrections -- are explored in the second part of this text. Historical and developmental aspects are considered, and each component is discussed in terms of its relationship to the criminal process. The traditional elements of the criminal process are reviewed by highlighting each of the major phases or justice-actors. Among the elements discussed are prosecution, bail, grand jury operations, and juvenile justice. Finally, such trends as diversion and overcriminalization are examined.